Synthesis method of monazite standard sample and double-method dating application
By preparing standard samples of phosphate glass with known U content, the problem of determining U element content in monazite was solved, and the accurate measurement of monazite uranium content and accurate acquisition of U-Pb age was achieved.
Patent Information
- Application Number
- CN202510068559.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The lack of standard samples with known U content matching the monolithic matrix in the prior art makes it difficult to accurately determine the U element content in monolithic, affecting the accurate determination of U-Pb age and fission track age.
A phosphate glass with known U content and good uniformity was prepared as a standard sample. The raw materials were weighed by stoichiometric ratio, and after multiple grinding, compacting, calcining and melting, a yellow transparent phosphate glass was formed. It was used to calibrate the relationship between ICP-MS signal strength and U element content of monazite, and to correct experimental errors such as instrument signal drift and mass fractionation.
Accurate measurement of uranium content of monolith is achieved, ensuring accurate acquisition of U-Pb age and fission track age, and improving the accuracy and reliability of measurement.
Smart Images

Figure CN119827258A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of monazite dating, and in particular to a method for synthesizing a monazite standard sample and a dual dating application. Background Art
[0002] Monazite is a phosphate mineral rich in radioactive elements such as U and Th. By measuring the concentration of uranium isotopes and their decay product Pb isotopes in monazite and using the decay equation, the U-Pb age of monazite can be obtained, thereby obtaining relevant information such as mineral crystallization and evolution. In the field of earth sciences, the age and thermal history of geological bodies can be obtained by measuring the concentration of radioactive elements and their decay products in monazite.
[0003] For example, CN116609421B relates to a dating method based on monazite fission track, which includes: etching a plurality of monazite samples; placing the etched plurality of monazite samples under a fission track analyzer for observation, counting the track density of each monazite sample, and marking the corresponding test position coordinates; according to the marked test position coordinates, using a laser ablation inductively coupled plasma mass spectrometer to laser ablate the monazite sample and the selected standard sample, and calculating the density of the monazite sample in the monazite sample according to the laser ablation data. 238 U content; according to the track density of each monazite sample, 238 The U content was analyzed to determine the fission track age of multiple monazite samples. This dating method breaks through the technical barrier that the external detector method cannot be used to determine the number of radioactive parent bodies due to the high Gd content and strong absorption of neutrons in monazite, and realizes the determination of the fission track age of monazite minerals, filling the gap in existing technologies.
[0004] In the above dating method, laser ablation inductively coupled plasma mass spectrometry (ICP-MS) is used for laser ablation. Laser ablation inductively coupled plasma mass spectrometry (ICP-MS) is a widely used isotope measurement method. When using the ICP-MS method to measure the concentration of a specific isotope in a sample, a sample with a known concentration of the element (i.e., a standard sample) is required to calibrate its intensity. In addition to determining the concentration, the element is also required to be evenly distributed in the standard sample. Currently, the commonly used standards for measuring silicate minerals include silicate glass standards such as NIST610. However, there is currently no such standard sample with a known U element concentration for monazite. Due to the matrix effect, glass NIST610 and the like cannot accurately calibrate the U element content in monazite (CePO4).
[0005] In summary, the technical difficulty in accurately determining the U concentration in the above-mentioned dating methods is due to the lack of standard samples for determining the U content of fission track matrix that match the monazite matrix.
[0006] In order to overcome the shortcomings of the existing technology, a phosphate glass with known U content and good uniformity was prepared as a standard sample to calibrate the relationship between the ICP-MS signal intensity and the U element content of monazite, and to correct experimental errors such as the instrument signal drift and mass fractionation of the laser and mass spectrometer, so as to achieve accurate measurement of the uranium content of monazite. Therefore, a method for synthesizing a monazite standard sample and its application in double dating were proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a method for synthesizing a monazite standard sample and its application in dual dating to solve the problems raised in the above-mentioned background technology.
[0008] To achieve the above object, the present invention provides a method for synthesizing a monazite standard sample, comprising the following steps: S1. Weigh cerium phosphate, uranium oxide, thorium dioxide, lead carbonate and phosphorus pentoxide according to the stoichiometric ratio of U, Th and Pb concentrations of the standard sample to be prepared, and grind them in a mortar until they become a uniform and fine flour-like powder; S2, after being compacted by a tablet press and put into a heating furnace for calcination, it is fully ground again, compacted and put into a heating furnace for calcination, and the cycle is repeated 3-4 times; S3, grinding the sample after the thermal cycle treatment thoroughly, mixing it with the flux in a ratio of 15:85, grinding it evenly, and pouring it into the crucible; S4. Place the crucible in a high-temperature furnace to fully melt and evenly mix the materials, then keep the heating furnace at 1400 degrees Celsius and quickly take out the crucible to quickly quench it to form a uniform yellow transparent phosphate glass.
[0009] As a further improvement of the technical solution, in S1, the material is fully ground in a mortar to form a uniform and fine flour-like powder of 280-320 mesh.
[0010] As a further improvement of the technical solution, in S2, the powder is ground and compacted and then placed in a heating furnace and calcined at 1200-1600 degrees Celsius for 24 hours.
[0011] As a further improvement of the present technical solution, in S3, the soldering flux is potassium metaphosphate.
[0012] As a further improvement of the present technical solution, in S3, the crucible is a platinum crucible.
[0013] As a further improvement of the technical solution, in S4, the platinum crucible is placed in a high-temperature furnace and maintained at 1200-1500 degrees Celsius for 24 hours.
[0014] Correspondingly, the synthesis method of the monazite standard sample is applied in double legal dating.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The synthesis method of the monazite standard sample and the application of the dual dating method include weighing raw materials according to the stoichiometric ratio of U, Th and Pb concentrations of the standard sample to be prepared, processing the raw materials into powder, grinding, compacting and calcining the powder for multiple times, and then fully melting and mixing with a solvent to form a yellow transparent phosphate glass, thereby artificially synthesizing and preparing a phosphate glass standard sample, so as to realize the measurement of U concentration in monazite by laser ablation-inductively coupled plasma mass spectrometry, and further realize the simultaneous and accurate acquisition of monazite U-Pb age and fission track age.
[0016] In addition to the synthesis method of the monazite standard sample and the application of the dual dating method, a data correction scheme for the U content of monazite was also proposed. A secondary correction strategy was used to calibrate the relationship between the monazite ICP-MS signal intensity and the U element content, and to correct experimental errors such as the instrument signal drift and mass fractionation of the laser and mass spectrometer, thereby achieving accurate measurement of the uranium content of monazite. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a flow chart of the present invention; Figure 2 This is a graph showing the U content test results of the sample of the present invention; Figure 3 It is a schematic diagram of the uniformity of U content of the standard glass of the present invention. DETAILED DESCRIPTION
[0018] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Solitary 238 Spontaneous fission of U will form damage in the mineral, namely fission tracks. After the tracks are enlarged to the micrometer level by chemical etching, the track density and length information can be counted under an optical microscope. 238 U is formed by fission, so the number of fission tracks is related to the 238 The change in the amount of U also conforms to the fission equation. 238 The fission track age of monazite can be obtained by the number of U and the number of spontaneous fission tracks.
[0020] In addition, when fission tracks are heated, the track length will shorten or even disappear (density decreases), which is called fission track annealing. By measuring the degree of fission track annealing, the thermal history of the mineral can be inverted, so this method is also called fission track thermochronology. It can be seen that whether it is to obtain the U-Pb age of monazite or the fission track age of monazite, it is necessary to accurately measure the 238 U content.
[0021] Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) is a widely used method for testing trace element content. Due to the presence of multiple error sources such as matrix effect, signal drift, and mass discrimination effect during the test process, accurate calibration and analysis of the signal collected by the mass spectrometer is required to obtain accurate sample trace element content data. The most commonly used data calibration method in actual work is to use external standard + internal standard element + standard sample crossover (SSB) joint calibration.
[0022] Among them, the external standards currently mostly use the NIST610 / 612 / 614 series of silicate glass standards artificially developed by the National Institute of Standards and Technology of the United States (Na, Al, Si and Ca are the main elements in NIST610, and the contents of Na2O, Al2O3, SiO2 and CaO are 13.4%, 1.95%, 69.7% and 11.4% respectively, and most of the other sixty trace elements are around 500ppm); the internal standard elements are generally selected as internal standards with relatively light major elements that are evenly distributed in minerals and have known concentrations (Longerich & Jackson, 1996; Paul et al., 2023; Walas et al., 2014), such as Si in zircon (ZrSiO4) and Ca in apatite (CaPO4).
[0023] Taking the determination of U content in zircon as an example, the specific test and correction methods are as follows: (1) Determine the signal intensity CPS of the internal standard element Si and the element to be measured in the external standard substance NIST610 by mass spectrometry 610-Si and CPS 610-U , and the signal intensity CPS of the internal standard element and the element to be measured in the sample sam-Si and CPS sam-U ; (2) Based on the above signal intensity, combined with the content of the internal standard element C in the external standard material NIST610 610-Si And the content of internal standard element C in the sample sam-Si , calculate the matrix effect difference coefficient K between the sample and the external standard substance, K=(CPS sam-Si / Csam-Si ) / ( CPS 610-Si / C 610-Si ); (3) Apply the above difference coefficient to the calculation of the element U to be measured, that is, K = (CPS sam-U / C sam-U ) / ( CPS 610-U / C 610-U ), since the U content in the external standard NIST610 is known, and the signals of NIST610 and the element U to be measured in the sample have been measured by the mass spectrometer, the U content in the sample can be calculated by the above equation C sam-U .
[0024] Therefore, there are several technical defects in the above test and correction scheme, which will lead to deviations in the test results: 1. Monazite is a phosphate mineral containing cerium (La) and lanthanum (Ce), with a molecular formula of (Ce, Y, La, Th)PO4. Compared with the above-mentioned NIST610 series standard materials, the matrix is very different. Whether the above-mentioned correction scheme can accurately correct the matrix effect deviation must be considered; 2. The major elements (%) in monazite are mainly Ce, La, Th and P. By comparing the content information of NIST standard glass, it can be found that the major elements in monazite are trace elements (ppm) in the NIST series of standard materials, and the content difference can be 4-5 orders of magnitude. This difference will inevitably lead to the correction deviation of the above correction scheme; 3. Currently, there is a lack of a standard sample with a known and uniform U concentration in monazite. There are only two natural single mineral standards 44069 and RW-1 (Ling Xiaoxiao et al., 2017) reported in the literature for U-Pb isotope dating of monazite. 44069 is a small particle sample with a diameter of only tens of microns. It has been used up internationally and is basically unavailable. RW-1 was published by the Institute of Geology and Geophysics, Chinese Academy of Sciences. It is difficult to use on a large scale even though its particles are slightly larger. In addition, there are inevitable defects in the homogeneity of natural minerals, making it difficult to carry out the above correction scheme.
[0025] In summary, the existing SiO2 glass standards NIST610 and NIST612 cannot accurately calibrate the U content in the phosphate mineral monazite. The present invention aims to overcome the existing deficiencies and prepare a phosphate glass with confirmed U content and good uniformity as a standard sample to calibrate the relationship between the ICP-MS signal intensity and the U element content of monazite, correct the experimental errors such as the instrument signal drift and mass fractionation of the laser and mass spectrometer, and thus achieve accurate measurement of the uranium content of monazite.
[0026] Therefore, please refer to Figure 1 As shown, the present invention aims to provide a method for synthesizing a monazite standard sample, comprising the following steps: S1. Weigh cerium phosphate (CePO4), uranium oxide, thorium dioxide (ThO2), lead carbonate (PbCO3) and phosphorus pentoxide (P2O5) according to the stoichiometric ratio of U, Th and Pb concentrations of the standard sample to be prepared, and grind them in a mortar to form a uniform and fine flour-like powder of 280-320 mesh; S2, after compacting by tablet press, put it into heating furnace and calcine it at 1200-1600 degrees Celsius for 24 hours, grind it again, compact it and put it into heating furnace for calcination, and repeat 3-4 times; S3, after the sample that has completed the heat cycle treatment is fully ground, it is mixed with a flux such as potassium metaphosphate (KPO3) in a ratio of 15:85, ground evenly, and poured into a platinum crucible. The mixing ratio of 15:85 can avoid the formation of CePO4 crystals during cooling and quenching; S4, placing the platinum crucible in a high temperature furnace at 1200-1500 degrees Celsius for 24 hours to allow all substances to be fully melted and evenly mixed, then quickly taking out the platinum crucible while maintaining the heating furnace at 1400 degrees Celsius to rapidly quench it to form a uniform yellow transparent phosphate glass, i.e., monazite standard glass; Then the prepared phosphate glass is divided into multiple batches, and data testing and uniformity inspection are performed on different batches of phosphate glass. The specific process of data testing and uniformity inspection is as follows: Step 1: Random U content determination experiments were conducted on different batches of phosphate glass. The test process adopted the conventional laser in-situ test process of monazite fission track and U-Pb dual dating. The test instrument was a laser ablation-quadrupole inductively coupled plasma mass spectrometer (LA-ICP-MS, models were ESL 193NWRUC and Agilent 7500a respectively); Step 2: Using the digestion method, the standard glass sample is subjected to solution method U content determination; Step 3: Verify the uniformity of the U content of the standard glass through the results of the in-situ random experiment; then verify the accuracy and precision of the laser in-situ determination of the U content by comparing the results of the laser in-situ and digestion sample solution methods.
[0027] The synthesis method of the monazite standard sample provided by the present invention and the application of the dual dating method are further described below by preparing a standard sample required for a dating method based on monazite fission track in patent publication number CN116609421B. Example
[0028] The purpose of this example is to prepare a batch of monazite standard samples with U and Th contents of about 145 ppm. The specific steps are as follows: S1. Weigh cerium phosphate (CePO4), uranium oxide, thorium dioxide (ThO2), lead carbonate (PbCO3) and phosphorus pentoxide (P2O5) according to the stoichiometric ratio of U, Th and Pb concentrations of the standard sample to be prepared, and grind them in a mortar to form a uniform and fine flour-like powder of 300 mesh; S2, after compacting by tablet press, put it into heating furnace and calcine it at 1400 degrees Celsius for 24 hours, grind it again, compact it and put it into heating furnace and calcine it, and repeat it 3 times; S3, grinding the sample after the heat cycle treatment thoroughly, mixing it with a flux such as potassium metaphosphate (KPO3) in a ratio of 15:85, grinding it evenly, and pouring it into a platinum crucible; S4, keeping the platinum crucible in a high temperature furnace at 1400 degrees Celsius for 24 hours, so that all substances are fully melted and evenly mixed, and then quickly taking out the platinum crucible while keeping the heating furnace at 1400 degrees Celsius, so that it is quickly quenched to form a uniform yellow transparent phosphate glass, i.e., monazite standard glass, to complete the preparation of the standard sample; The masses of some raw materials used in this experimental example and the concentrations of U and Th elements to be calibrated are shown in Table 1.
[0029] Table 1: The mass of some raw materials used in this experiment and the concentration of U and Th elements to be calibrated raw material Weighing mass (g) Concentration of element to be calibrated (ppm) <![CDATA[Cerium phosphate (CePO4)]]> 5.0003 - <![CDATA[Uranium oxide (U3O8)]]> 0.0057 143 <![CDATA[Thorium dioxide (ThO2)]]> 0.0057 148 <![CDATA[Potassium metaphosphate (KPO3)]]> 28.3 - After the preparation is completed, some small pieces of glass solid are randomly taken out from the crucible, and the laser in-situ micro-area U content is measured by LA-ICP-MS to verify the uniformity of the U content of the monazite standard glass: Randomly select the prepared standard glass blocks and carry out the following laser in-situ micro-area measurement sample preparation process: (1) First, heat the heating table to 170 degrees (the temperature that can melt the glue); (2) Glue the sample onto the polishing sample table; (3) Align the sample with the screws on both sides of the polisher; (4) Use the polisher to gently polish a flat surface on the polishing paper using the "8" grinding method. Use 1200-grit sandpaper for rough polishing first, then 2400-grit and 4000-grit for fine polishing in turn. (5) Finally, polish the surface with polishing paper to get a scratch-free bright surface; (6) Remove the ejected sample, place the glass slide on the heating table to melt the glue, place the sample on the glue, and remove the glass slide from the heating table.
[0030] From September 2024 to December 2024, some standard glass sample particles were randomly selected for laser in-situ micro-area U content determination experiments and data correction: (1) On September 23, 2024, a small sample was randomly selected and a test sequence of 20 test points was randomly established. The original data number was 2024I23p00.B. The average value of the U content test at the 20 test points after correction was 167.00±3.58ppm; (2) On October 18, 2024, two small samples were randomly selected. One was prepared into a conventional 1-inch circular resin target, and the other was directly glued to a glass slide. A test sequence was randomly established. A total of 30 test points were tested for the two samples. The original data number was 24J18r00.B. The U content test results of the two samples were consistent. The average value of the 60 test points after correction was 154.39±3.60ppm. (3) On October 28, 2024, three small samples were randomly selected, glued to a glass slide and polished, and then randomly tested at 30 points. The original data number was 24J28k00.B. The calibration results of the U content test at 90 points were consistent, with an average value of 163.56±1.92ppm; (4) On November 12, 2024, two small samples were randomly selected, glued to a glass slide and polished, and then tested on a machine at 30 points. The original data number was 24K12o00.B. The calibration results of the U content test at 60 points were consistent, with an average value of 173.80±1.36ppm; (5) On November 13, 2024, two small samples were randomly selected, glued to a glass slide and polished, and then tested on a machine at 30 points. The original data number was 24K12o00.B. The calibration results of the U content test at 60 points were consistent, with an average value of 156.55±1.44ppm; (6) On November 14, 2024, two small samples were randomly selected, glued to a glass slide and polished, and two on-machine test sequences were established. The original data numbers were 24K14p00.B and 24K14r00.B, respectively. 30 sample measurement points were completed respectively. The average U content of the 30 measurement points in the first sequence was 159.33±2.17ppm, and the second sequence was 155.40±1.33ppm; (7) On December 9, 2024, two small samples were randomly selected, glued to a glass slide and polished, and then tested on the machine at 30 points. The original data number was 24L09o00.B. The calibration results of the U content test at 60 points were consistent, with an average value of 166.07±5.93ppm; In summary, in the past three months, a total of 13 small samples were selected, 8 test sequences were randomly completed, and a total of about 410 test points were measured. The test results are as follows: Figure 2 , Figure 3As shown, the average value of the 8 test sequences is 161.94ppm, the absolute external precision is 0.67ppm, and the relative external precision is 0.41%, which effectively proves that the U content uniformity of the standard glass is good.
[0031] Accuracy test of U content in standard glass: Two small pieces of standard glass samples were randomly selected and tested in the Rock and Mineral Sample Preparation and Analysis Laboratory of the Institute of Geology and Geophysics, Chinese Academy of Sciences. The test instrument was the ThermoFisher icap RQ inductively coupled plasma mass spectrometer. Two parallel experiments were carried out and the test results were 161.455ppm and 158.075ppm respectively. The measurement results are completely consistent with the above-mentioned laser in-situ micro-area measurement results within the error range.
[0032] In the present invention, raw materials are weighed according to the stoichiometric ratio of U, Th and Pb concentrations of the standard sample to be prepared as needed, and the raw materials are processed into powder, and then ground, compacted and calcined for multiple times, and then fully melt-mixed with a solvent to form a yellow transparent phosphate glass, so as to artificially synthesize and prepare a phosphate glass standard sample, so as to realize the measurement of U concentration in monazite by laser ablation-inductively coupled plasma mass spectrometry, and further realize the simultaneous and accurate acquisition of monazite U-Pb age and fission track age.
[0033] In addition, the present invention also proposes a data correction scheme for the U content of monazite, which adopts a secondary correction strategy: first, NIST610 silicate glass is used as an external standard, Ce is used as an internal standard element (the Ce content of the monazite standard glass adopts the calculated value of 88087ppm in the original formula), and the Iolite data analysis software is used to obtain a first-corrected U content result; then, the UO2 content of 0.3% in the monazite U-Pb dating standard RW-1 (the internal standard element Ce content is 25.22%) reported in the document Ling (2017) is used to perform a second correction on the U content result after the NIST610 correction, that is, to calibrate the relationship between the monazite ICP-MS signal intensity and the U element content, and to correct the experimental errors such as the instrument signal drift and mass fractionation of the laser and mass spectrometer, so as to achieve accurate measurement of the uranium content of monazite.
[0034] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for synthesizing a monazite standard sample, characterized in that: The following steps are involved: S1. Weigh cerium phosphate, uranium oxide, thorium dioxide, lead carbonate and phosphorus pentoxide according to the stoichiometric ratio of U, Th and Pb concentrations of the standard sample to be prepared, and grind them in a mortar until they become a uniform and fine flour-like powder; S2, after being compacted by a tablet press and put into a heating furnace for calcination, it is fully ground again, compacted and put into a heating furnace for calcination, and the cycle is repeated 3-4 times; S3, grinding the sample after the thermal cycle treatment thoroughly, mixing it with the flux in a ratio of 15:85, grinding it evenly, and pouring it into the crucible; S4. Place the crucible in a high-temperature furnace to fully melt and evenly mix the materials, then keep the heating furnace at 1400 degrees Celsius and quickly take out the crucible to quickly quench it to form a uniform yellow transparent phosphate glass.
2. The method for synthesizing a monazite standard sample according to claim 1, characterized in that: In S1, the mixture is fully ground in a mortar to form a uniform and fine flour-like powder of 280-320 mesh.
3. The method for synthesizing a monazite standard sample according to claim 1, characterized in that: In S2, the powder is ground and compacted and then placed in a heating furnace for calcination at 1200-1600 degrees Celsius for 24 hours.
4. The method for synthesizing a monazite standard sample according to claim 1, characterized in that: In S3, the soldering flux is potassium metaphosphate.
5. The method for synthesizing a monazite standard sample according to claim 1, characterized in that: In the above S3, the crucible is a platinum crucible.
6. The method for synthesizing a monazite standard sample according to claim 1, characterized in that: In S4, the platinum crucible is placed in a high temperature furnace and maintained at 1200-1500 degrees Celsius for 24 hours.
7. Application of the method for synthesizing a monazite standard sample according to any one of claims 1 to 6 in double dating.
Citation Information
Patent Citations
Dating methods based on monazite fission tracks
CN116609421B
Method for preparing rare earth doped sodium yttrium tungstate crystals applied to quantitative calibration materials
CN110184648A
Preparation method and application of dolomite solid standard sample
CN115479822A
Thorium-lead age testing method for niobium-tantalum-iron ore
CN116559273A
Dating method based on monazite fission track
CN116609421A